2021
DOI: 10.3389/fenrg.2021.786659
|View full text |Cite
|
Sign up to set email alerts
|

Nexus Between Green Finance, Energy Efficiency, and Carbon Emission: Covid-19 Implications From BRICS Countries

Abstract: The threats of climatic change on life, health, and the environment have been regarded by the joint consensus of scholars in the recent decades. With the advancement of global green development, green finance has paved the way for the government to respond to the challenges of climate change by providing mature financial services, appropriate financing, investment, and project funds related to environmental protection. In this context, green finance was proposed, and the relationship between green finance, ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 64 publications
2
15
0
Order By: Relevance
“…The development of new renewable energy sources has a huge influence on CO 2 emissions, which means that the world should invest more in R&D to find ways to minimize these emissions. A similar conclusion was reached by Koçak andUlucak (2019), Álvarez-Herránz et al (2021), and Wang et al (2019Wang et al ( , 2021. Public-private partnership investments in renewable energy are increasing because of the negative effects on CO 2 emissions that The overall GDP of a region has a considerable influence on CO 2 emissions, which indicates that the output rise is connected to the increased usage of energy; according to this study, renewable energy sources should be given greater weight and attention to address the problem.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The development of new renewable energy sources has a huge influence on CO 2 emissions, which means that the world should invest more in R&D to find ways to minimize these emissions. A similar conclusion was reached by Koçak andUlucak (2019), Álvarez-Herránz et al (2021), and Wang et al (2019Wang et al ( , 2021. Public-private partnership investments in renewable energy are increasing because of the negative effects on CO 2 emissions that The overall GDP of a region has a considerable influence on CO 2 emissions, which indicates that the output rise is connected to the increased usage of energy; according to this study, renewable energy sources should be given greater weight and attention to address the problem.…”
Section: Discussionsupporting
confidence: 75%
“…Those who oppose globalization believe that the environmental impacts are two-fold. First and foremost, pollution havens occurs when trade reforms of liberalization enable polluting industries to be relocated to regions with less stringent regulatory controls (Wang, Huang, and Xiang, 2021). It is also likely that pollution will rise in low-income or emerging nations as a result of globalization until they reach a certain degree of economic development.…”
Section: Introductionmentioning
confidence: 99%
“…also did some digging and investigated the role of green bond financing in carbon reduction, the results showed the significant relation, however, the study did not propose any policy for sustainable development. Wang et al (2021) also added their contribution by providing a comprehensive view regarding the significance of green bond in the development of low-carbon society. The study offered some suggestions that are of equally important to achieve low carbon goal.…”
Section: Green Finance and Carbon Emissionsmentioning
confidence: 99%
“…Thus, green investment is essential for low carbon emissions in the environment. Wang et al (2021) explored the link between renewable energy, green finance, and CO 2 pollutants with other controlling variables in BRICS countries from 2000 to 2018. The results showed that green finance and renewable energy increase carbon neutrality while trade openness, economic growth, and foreign direct investment stimulate CO 2 emissions.…”
Section: Green Energy Investment and Environmental Degradationmentioning
confidence: 99%